2018
DOI: 10.1002/jqs.3020
|View full text |Cite
|
Sign up to set email alerts
|

What does the occurrence of Sporormiella (Preussia) spores mean in Australian fossil sequences?

Abstract: Understanding the loss of the final few species of Australian megafauna is beset by a paucity of data on human arrival, well‐provenanced megafauna, human/megafauna population range and distribution (coexistence and interaction), and the range, scale and impact of environmental changes spanning the human–megafauna period. To overcome these shortcomings, the occurrence and decline of coprophilous fungal spores of Sporormiella in sediments have been used as a proxy for extinct megaherbivores. The Sporormiella evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…Reduction of the Sporormiella dung fungus occurring around 41 ka at Lynch's Crater,~560 km north of SWC, has been used as a proxy for both the presence of megaherbivores and their rapid population decline to extinction 15,16 . However, the use of Sporormiella as a megaherbivore proxy has been challenged on taphonomic and biological grounds 10,18,19,50,51 . Variable concentrations of Sporormiella spores are present in the sediment samples taken at SW9 for palynological assessment (Supplementary Note 9, Supplementary Table 23).…”
Section: Supplementary Notes 5-8)mentioning
confidence: 99%
See 1 more Smart Citation
“…Reduction of the Sporormiella dung fungus occurring around 41 ka at Lynch's Crater,~560 km north of SWC, has been used as a proxy for both the presence of megaherbivores and their rapid population decline to extinction 15,16 . However, the use of Sporormiella as a megaherbivore proxy has been challenged on taphonomic and biological grounds 10,18,19,50,51 . Variable concentrations of Sporormiella spores are present in the sediment samples taken at SW9 for palynological assessment (Supplementary Note 9, Supplementary Table 23).…”
Section: Supplementary Notes 5-8)mentioning
confidence: 99%
“…However the validity of fungal spores as useful proxies for megafauna requires cautious interpretation due to the numerous factors impacting their dispersal and survival into the fossil record, including taphonomic, sedimentological and biological considerations 17,18 . Without a clear link between Sahul megafauna and these dung fungi its utility as a robust proxy is equivocal 10,19 .…”
mentioning
confidence: 99%
“…Some authors now treat Sporormiella and Preussia as synonyms, due to identical diagnostic morphological features and habitat preferences (e.g. Arenal et al, 2004;Dodson and Field, 2018).…”
Section: Sporormiella Analysismentioning
confidence: 99%
“…In recent years, however, the range of abiotic factors that can influence taphonomic processes in sedimentary settings has been subject to increasing scrutiny because of their potential impact on spore preservation and representation (Baker et al, 2013;Dodson and Field, 2018). For example, a study of modern sediments from a suite of different-sized lakes in Florida by Raper and Bush (2009) suggested that proximity of the core site to the shoreline was important.…”
Section: Introductionmentioning
confidence: 99%
“…A study of Preussia abundance in New Zealand demonstrated that this technique, which had previously been applied to mammalian megafauna in continental regions, was similarly effective for investigating past abundances of avian megafauna within island contexts (Wood et al 2011). This technique has proven controversial, however, with species identifications and accumulation rates under varying hydrological conditions all subject to debate (Johnson et al 2015, Dodson and Field 2018). Nevertheless, the introduction of fecal biomarker analysis, when combined with other paleoenvironmental indicators such as pollen and sedimentary DNA, may in future support inferences about megafaunal population abundance from sedimentary records.…”
Section: Microscopy and High-resolution Imagingmentioning
confidence: 99%